Utility of contrast-enhanced ultrasound for assessing disease activity in takayasu arteritis with carotid artery involvement: a scoping review - Soto-Fajardo, Carina; Cervantes-Ramírez, Rosa-Elena; Montiel-Castañeda, Carlos-Vidal; Morales-Meza, Ada-Rocío; Rojas-Abarca, Daniela-Isabel; Sánchez-Zamudio, Fabiola-Bugambilia; Sandoval, Hugo; Pineda, Carlos (Frontiers in Immunology, 2026)
Takayasu arteritis (TA) is a chronic, immune-mediated vasculitis that primarily affects the large arteries, particularly the aorta and its main branches, leading to stenosis, occlusion, dilation, or aneurysms. Traditional imaging modalities, including computed tomography angiography (CTA), magnetic resonance angiography (MRA), and positron emission tomography/computed tomography (PET-CT), offer valuable diagnostic information; however, their clinical applicability has limitations, including high costs, radiation exposure, and reduced availability. In recent years, contrast-enhanced ultrasound (CEUS) has emerged as a minimally invasive, radiation-free technique capable of detecting vascular wall neovascularization as a potential surrogate imaging marker of TA inflammatory activity.ObjectiveThis scoping review, conducted in accordance with the Joanna Briggs Institute (JBI) methodology and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) checklist, aims to synthesize current evidence on the diagnostic and monitoring utility of CEUS in patients with TA and carotid involvement.MethodsWe systematically searched MEDLINE/PubMed, Scopus, Web of Science, LILACS and EBSCO from inception to May 2025 for original studies of adult patients with TA in whom CEUS was used to assess disease activity.ResultsEighteen studies (8 cross-sectional, 3 cohort, 7 case reports; 631 patients) met the eligibility criteria. Across these studies, CEUS detected arterial wall neovascularization compatible with active inflammation, particularly in the carotid arteries, and demonstrated moderate-to-strong correlations with inflammatory biomarkers, PET-CT findings, and clinical activity scores such as the Indian Takayasu Activity Score (ITAS) and the National Institutes of Health (NIH) criteria. Importantly, CEUS can reveal subclinical or residual inflammation even when clinical symptoms or laboratory markers are absent. Its ability to detect early relapses and monitor therapeutic response has been demonstrated in both observational cohorts and individual case reports. Despite this, substantial heterogeneity in imaging protocols and activity definitions limits comparability across studies and restricts integration into clinical practice.ConclusionCEUS is a minimally invasive, reproducible, and effective technique for both detecting and monitoring disease activity in TA with carotid vessel involvement, thereby facilitating early and accurate therapeutic decisions. Its future incorporation into clinical practice will require validated scoring systems, harmonized acquisition protocols, and demonstration of added value in treatment decision-making and long-term outcomes.